Biofilm‐induced bioclogging produces sharp interfaces in hyporheic flow, redox conditions, and microbial community structure. Issue 10 (29th May 2017) - Caruso, Alice; Boano, Fulvio; Ridolfi, Luca; Chopp, David L.; Packman, Aaron
Abstract: Riverbed sediments host important biogeochemical processes that play a key role in nutrient dynamics. Sedimentary nutrient transformations are mediated by bacteria in the form of attached biofilms. The influence of microbial metabolic activity on the hydrochemical conditions within the hyporheic zone is poorly understood. We present a hydrobiogeochemical model to assess how the growth of heterotrophic and autotrophic biomass affects the transport and transformation of dissolved nitrogen compounds in bed form‐induced hyporheic zones. Coupling between hyporheic exchange, nitrogen metabolism, and biomass growth leads to an equilibrium between permeability reduction and microbial metabolism that yields shallow hyporheic flows in a region with low permeability and high rates of microbial metabolism near the stream‐sediment interface. The results show that the bioclogging caused by microbial growth can constrain rates and patterns of hyporheic fluxes and microbial transformation rate in many streams. Key Points: Biofilm‐induced bioclogging strongly regulates hyporheic pore water flow and microbial transformation rates Bioclogging is primarily induced by growth of heterotrophic bacteria within pore space Feedbacks associated with microbial metabolism and growth generate sharp fronts in hyporheic flow, redox conditions, and microbial biomass